Model Examples Non Examples, Ind THE IMPROVEMENT DESCRIPTION WRITING SKILLS THROUGH THE EXAMPLES NON EXAMPLES MODEL FOR THE FIFTH GRADE STUDENTS OF SDN SETU 01 PAGI JAKARTA STATE ELEMENTARY SCHOOL ACADEMIC - Sr Nurafifah (Indonesian Journal of Education Teaching and Learning (IJETL), 2023)
The purpose of this research is to improve writing description skills in the fifth grade students of SDN Setu 01 Pagi Jakarta The Examples Non Examples Model.This research was a classroom action research, it conducted in two cycles. Each cycle consisted of four phases, namely: planning, implementation, observation, and reflection. The subjects of this research were the fifrth grade students as many as of SDN Setu 01 Pagi Jakarta as many as 32 students and the teachers of SDN Setu 01 Pagi Jakarta. The data of this research were colected from the teacher and the students through observation, interview, documentation, and test. The data is validity used were source triangulation and technique triangulation. The results of the pretest showed that the writing description skills is only 31,25% with the minimum learning completeness. Following the treatment, the class minimum learning completeness increase become 43,75% in a cycle I, and 90,62% in cycle II. Based on the research results, a conclusion is drawn that Examples Non Examples Model can improve the skill of writing description on the students in grade V of SDN Setu 01 Pagi Jakarta